Geometrical Derivation of Differential Kinematics to Calibrate Model Parameters of Flexible Manipulator. (7th February 2013) - Lee, Bum-Joo
In this paper differential kinematics was geometrically derived to be utilized in a calibration algorithm that improves the accuracy of the manipulation of a robot. Even though the mechanical components are manufactured and assembled precisely, small differences between the designed and the actual system always exist, due to both geometric and unmodelled errors. In order to resolve these problems, differential relationships between the model parameters and the end-effector's posture were formulated. Subsequently, a derivative based estimation algorithm, such as an EKF (Extended Kalman Filter) manner, could be adopted to update the model parameters. The proposed algorithm includes joint flexibility, so is an advanced version of previous work, where a rigid joint model was adopted [1 ]. The effectiveness of the proposed algorithm was verified by a computer simulation with a 6 DOF manipulator robot.